Antebellum Sensational Novels and Subversion of Domesticity - Jozef Pecina (American and British Studies Annual, 2010)
With the sensational novels of the 1840s, a new genre of popular fiction focused on life in cities appeared in America. Through grotesque humor, repulsive images and at times extreme perversity the authors of these novels intended to unmask the corruption and decadence of the ruling class. The first part of this article traces the development of sensational novels and the achievements George Thompson, the most prolific author in this genre. The second part of the article focuses on the subversion of domesticity in Thompson’s novels. Domestic novels of 19th century usually trace the success of a virtuous heroine who overcomes all kinds of difficulties and personal misfortune and, often guided by a strong Christian faith, moves to middle-class marriage. The sensational novels of George Thompson move in a different direction and subvert social norms of the era. His narratives deconstruct marriage and family, with households frequently being split apart as a result of the perverse activities of one or both spouses. Thompson’s novels do not end in domestic bliss, but with sensational and disturbing images. In this article I focus on the subversion of domesticity in two of Thompson’s novels – Venus in Boston and City Crimes.